A Case of Metastatic Renal Cell Carcinoma Presenting with Acute Disseminated Intravascular Coagulation - Yıldırım, Nılgun; Yıldırım, Erkan; Günay, Fatma; Merter, Mustafa (My University, 2023)
Disseminated intravascular coagulation (DIC) is a clinic pathological syndrome characterized by bleeding, thrombosis, or both, which are laboratory signs of coagulation and activation of fibrinolytic systems. This study focused on a case of acutely presenting DIC, which is a very rare complication of renal cell carcinoma (RCC). The patient was a 48-year-old male admitted to the emergency room due to shortness of breath and hemoptysis in the last couple of days. Computed Tomography scans indicated bilateral pulmonary nodules (metastasis), hypodense thrombus in the left pulmonary artery branch, thrombus in the right atrium and right ventricle, solid lesion (RCC?) in the right kidney lower pole. The patient was diagnosed with acute DIC with clinical and laboratory findings. Supportive therapy was initiated, a transbronchial biopsy was performed from the pleural lesion, and the patient was diagnosed with RCC. Pazopanib 400 mg (1x2) was prescribed. The patient responded quickly to the treatment and was clinically relieved. In the second month of treatment, the patient died from massive hemoptysis due to DIC. Acute DIC occurrence due to solid tumors is rare, but has a very poor prognosis. The treatment of underlying disease for DIC is the most effective approach in cancer patients. In the literature there is only one case of RCC-related acute DIC, who had a very short survival time as our case had.
Keywords: Therapy; Disseminated Intravascular Coagulation; Pazopanib; Clear Cell Renal Cell Carcinoma; Cardiac Thrombus